Treatment of Gingival Recession by Lateral Positioned Pedicle Graft: A Case Report - Abhaya Chandra Das1, Sourav Panda1, Manoj Kumar1, Anurag Satpathy2, Rashmita Nayak2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Gingival recession (GR) is a condition in which there is an apical shift of gingival margin leading to exposureof root surface. On exposure of root surface, there will be root sensitivity, pain, root caries, poor aesthetic,and ultimately tooth loss. There are various techniques used to treat gingival recession. In this case report,a laterally positioned pedicle graft technique was used to treat gingival recession. A 37-year-old male cameto the Department of Periodontics, with a chief complaint of sensitivity in lower left front teeth regions.On clinical examination, there was Miller Class III in 33 with the presence of generalized mild plaque andcalculus. It was planned for phase I therapy followed by phase II therapy. So scaling and root planing wasperformed to reduce inflammation and after 4 weeks, lateral positioned pedicle graft technique was doneunder infiltration local anesthesia. The subject was instructed to maintain oral hygiene. After 2 months, itwas found significant coverage of root with keratinized gingiva. He was very satisfied with the result.